Search Frictions, Competing Mechanisms and Optimal Market Segmentation - Xiaoming Cai; Pieter Gautier; Ronald Wolthoff (Tinbergen Institute, 2016)
In a market in which sellers compete for heterogeneous buyers by posting mechanisms, we analyze how the properties of the meeting technology affect the allocation of buyers to sellers. We show that a separate submarket for each type of buyer is the efficient outcome if and only if meetings are bilateral. In contrast, a single market with all agents is optimal if and only if the meeting technology satisfies a novel condition, which we call "joint concavity." Both outcomes can be decentralized by sellers posting auctions combined with a fee that is paid by (or to) all buyers with whom the seller meets. Finally, we compare joint concavity to two other properties of meeting technologies, invariance and non-rivalry, and explain the differences.
Keywords: C78; D44; D83; 330; search frictions; matching function; meeting technology; competing mechanisms; heterogeneity